Therapists’ perceptions of alliance barriers in the parent–therapist relationship when treating children who have experienced trauma - Simene Joffe; Veronica M Dwarika (Australian Journal of Psychology, 2025)
Objective Childhood experiences of traumatic events are common in all countries, and children may require psychotherapy after a traumatic experience. For those children who have experienced trauma and are involved in therapy, the parent–therapist relationship is important in promoting child trauma recovery. However, alliance barriers can interrupt the working relationship, compromising child treatment efficacy. Few studies have explored therapists’ perceptions of the complexities in the parent–therapist relationship when treating children for trauma.Method This exploratory study uses trauma theory to understand obstacles interfering with the parent–therapist alliance. Qualitative research methods were used to explore data obtained from 15 therapists. An interpretive phenomenological research design supported the study to answer the research question.Results Therapists were motivated to work with parents, as they recognise the important role of parents in treatment. They identified alliance barriers as reduced parent investment, parent trauma and therapists’ emotions. Therapists also applied a trauma-informed framework to moderate alliance obstacles preventing them from impacting child treatment success.Conclusion The findings highlight that therapists require knowledge of trauma theory and expertise in trauma-informed practice to work effectively with parents when treating children for trauma. This new knowledge will help therapists manage and support the parent–therapist relationship when treating children who have experienced trauma, improving long-term treatment outcomes of child psychotherapy.